Factors Affecting the Correct of Breastfeeding Teqnique - Husnul Muthoharoh; Indah Kurniawati (MBUnivPress, 2023)
Breastfeeding is a natural process, almost all mothers can breastfeed their babies without help from others. However, not all mothers can breastfeed with the correct technique. This research study aims to determine the factors that influence the correct breastfeeding technique in Karangcangkring village, Dukun, Gresik. The research design used was a quantitative analytical survey with a cross sectional approach which aims to determine the factors that influence the correct breastfeeding technique in mothers in one period of time, the location of this study was in Karangcangkring Village, Dukun, Gresik. The statistical test used in this study was Chi Square, the population in this study was all primiparous mothers who breastfed their babies in Karangcangkring Village, Dukun, Gresik, this study used a sampling technique with nonprobability sampling with accidental sampling type. The number of samples was 37 breastfeeding mothers who were studied from age, education level, occupation, and maternal knowledge. Research obtained from 37 respondents, obtained 20 people (66.7%) in breastfeeding mothers aged > 30 years have the correct breastfeeding technique with P value 0.01, breastfeeding mothers who have secondary and higher education have the correct breastfeeding technique as many as 9 people (24.3%) with P value 0.02. Breastfeeding mothers who work outside the home have correct breastfeeding techniques as many as 12 people (32.4%) with P value 0.03, who have high knowledge have correct breastfeeding techniques as many as 14 people (37.8%) with P value 0.02. There is a significant relationship between age, education, occupation, knowledge with the correct breastfeeding technique.